Creating JATS XML from DOCX (PUBMET, 2023)
JATS XML (Journal Article Tag Suite) is an adopted XML format used for publishing scientific and scholarly content. It is an alternative way of publishing contemporary scientific and professional journals, which has multiple advantages over traditional publishing methods.One of the key advantages of JATS XML is its ability to enhance the discoverability and accessibility of journal articles. This is achieved through the use of metadata tags, which provide a standardized way of describing content and make it easier for search engines to index and retrieve articles. Additionally, the use of JATS XML allows for better preservation of content and ensures that articles are machine-readable and easily integrated with other scholarly resources.Another significant advantage of JATS XML is its ability to facilitate publishing workflows, but unfortunately although it should be the case, currently that ability is not fully realized. Despite providing a standardized structure for content, which theoretically makes it easier for publishers to manage the publication process, some challenges still exist in the practical implementation of JATS XML. Creating JATS XML requires a lot of time if the editor writes XML from scratch or significant financial resources that need to be invested in purchasing professional tools or outsourcing this work. There are almost no free and effective tools for creating complete and correct JATS XML.The team from SRCE – University of Zagreb, University Computing Centre behind the HRČAK portal decided to adapt the universal document converter called Pandoc primarily for editors and publishers in HRČAK, but with the intention that in the future it can also be used by the wider scientific and professional community. At this workshop, we will introduce the process of creating JATS XML as part of HRČAK which will allow journal editors and publishers to create JATS XML more easily. The goal of is to allow users to create complete and correct JATS XML files for their journals through a simple interface without any prior knowledge of XML.
Keywords: conversion; discoverability; JATS XML; metatags; publishing